The effect of inflation, financial performance, and profit management on financial distress on property, real estate, and building construction companies listed on the Indonesia stock exchange - Dwi Dewianawati; Erry Setiawan (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine how significant the effect of inflation, financial performance, and earnings management on financial distress. The population in this study is the annual report of the Property, Real Estate, and Building Construction Sector Companies in Indonesia registered with Bank Indonesia during the period 2017-2021 as many as 45 companies. The analysis technique uses multiple linear regression. From the research that has been done and the discussion of the research results in the previous chapter, conclusions can be drawn from the research, namely: Inflation does not contribute to financial distress in property, real estate and building construction sector companies. Liquidity does not contribute to financial distress in property, real estate and building construction sector companies. Return On Equity contributes to Financial Distress in property, real estate and building construction sector companies. Return on Assets contributes to Financial Distress in property, real estate and building construction sector companies. Earnings management does not contribute to financial distress in property, real estate and building construction sector companies